Analysis of cultural identity mix within Chinese banks operating in South Africa - Mongalo, Theodora Thandekile (University of the Witwatersrand, Johannesburg, 2023)
Banking in South Africa has evolved with the internationalisations of banks over the years. As at 31 December 2021, there were 31 banks operating in South Africa. Of these, 13 were local branches of foreign banks, employing both home and host country nationals. The blend of nationalities in these banks results in a cultural mix. The aim of the study is to understand structural consensus in a setting that has a cultural mix. The structural consensus theory states that socialisation within a setting is guided by rules and behaviour, and these form the culture in the setting. To understand this, the researcher analysed the cultural identity mix in a Chinese bank operating in South Africa, guided by the work- related cultural dimensions used in studies of cross cultures. The cultural dimensions were applied to communication, conflict management, decision making, leadership and employee satisfaction. The study followed a deductive approach, on a single case study which allowed the researcher deep engagement with participants. Qualitative data was collected by way of semi-structured interviews from participants, representative of the cultural identity mix in the case. Focus was on understanding how cultural values affect communication, conflict and conflict management, decision making and leadership support. The aim of the researcher was to verify whether the assumption in the literature on cultural dimensions hold, in the selectedcase and how / if there is cultural consensus and social consensus. The data collected was analysed through the application of Colaizzi’s strategy, a data analysis method that allows for exhaustive approach to understanding the everyday lived experience in a social setting. The study reveals some similarities and some differences in the cultural values and beliefs of Chinese and South Africans. The two national cultures were found to display different values when communicating. These differences create barriers to social order. The cultural identity mix further displayed conflicting values in their approach to conflict and conflict management. The adopted values to conflict and conflict management are those of the Chinese culture and this creates an illusion of social order. Hierarchy was found to play an important role in decision making and involvement in the decision making process. Both cultures displayed respect for hierarchy and therefore there was social order when it comes to decision and decision making. Leadership and the support they offer was situational and supported the theory that states that leaders create a culture within an organisation. The outcomes of the study will contribute to existing literature and close gaps in existing literature. The first contribution is that culture is innate, secondly cultural dimensions can be partially used to explain cultural values, but they necessarily reflect the values of individuals. The study also provides support that culture is learnt and this results in tools for cultural and social consensus where there is a cultural identity mix. Another contribution of the study is the understanding of the Chinese and South African national culture, and emphasis on the strong cultural values of Confucianism for Chinese and Ubuntu for South Africans. Future research is recommended to focus on limitations of the study which include a replication of the study on a different population in order to add to the dependability and credibility of the results. Another recommendation is for a study that distinguishes between the various sub- cultures within the blanket South African culture
A dissertation submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, in fulfilment of the requirements of the degree of Masters of Commerce,University of the Witwatersrand, Johannesburg, 2023
Keywords: Cultural identity mix; Banking; Chinese; South Africa; Banking in South Africa; Foreign banks; UCTD; SDG-8: Decent work and economic growth